Evaluation of analgesic and neuropharmacological properties of the aerial part of Tinospora cordifolia Miers. in mice (Stamford Journal of Pharmaceutical Sciences, 2010)
Tinospora cordifolia Miers. is used in the Ayurvedic system of medicine for the treatment of jaundice, diabetes, and rheumatoid arthritis, and is also used as memory enhancer. But still there is no report of analgesic and neuropharmacological activities of the plant. For this reason, the present study was designed to evaluate analgesic and neuropharmacological activities of methanol extract of the aerial parts of Tinospora cordifolia. Analgesic activity of the crude extract at the dose of 200 and 400 mg/kg b.w. was evaluated for its central and peripheral pharmacological actions using hotplate and tail flick tests and acetic acid-induced writhing test respectively in mice. The extract produced a significant (p < 0.05-0.001) increase in pain threshold in hotplate and tail flick tests in a dose dependent manner. In acetic acid-induced writhing test the extract at both doses produced significant (p < 0.001) inhibition of writhing reaction but maximum inhibition (65.01%) of writhing was found at 400 mg/kg dose compared to the reference drug Diclofenac-Na at the dose of 10 mg/kg b.w. (77.07%). Neuropharmacological activity of the extract was also evaluated using rodent behabioural models; hole cross to evaluate motor activity, open field to evaluate exploratory behaviour and thiopental sodium-induced sleeping time to evaluate sedative potential of the extract. The extract significantly (p < 0.05-0.001) decreased motor activity and exploratory behavior of mice in hole cross and open field test respectively. The extract also produced rapid onset and maximized the duration of sleeping time when administered with thiopental sodium. Results of this study suggest that the aerial part of T. cordifolia possesses significant analgesic and CNS depressant activity.  Key words: Tinospora cordifolia; Menispermaceae; Analgesic; Neuropharmacological.DOI: 10.3329/sjps.v2i2.5822Stamford Journal of Pharmaceutical Sciences Vol.2(2) 2009: 31-37